PENGARUH PRODUK DAN SISTEM BISNIS TERHADAP KEPUTUSAN PEMBELIAN USAHA WARALABA ES TEH POCI DI KOTA SEMARANG - Nida Attaqia; Rodhiyah Rodhiyah (Universitas Diponegoro, 2016)
Policies, strategies and patterns to develop business through a franchise system Es Teh Poci is a franchise that is widely spread in Indonesia, including in the city of Semarang. Many of the factors that influence purchase decisions undertakings franchise, one of these products and systems business. The research aims to know the influence of products and business system against purchasing decisions undertakings franchise Es Teh Poci in Semarang city either partially or simultaneous. The primary data used by giving questionnaires to frinchisee with a total of 37 respondents determined using table formula Stephen Isaac & William B. Michael. Respondents taken using a simple random sampling method. Results and discussion. Products against ice tea Teapot well with average score 3.94, business system quite well with the average score 3.93 and purchase decisions with a high average score 3.71. Significant effect against the product purchase decisions (p < 0.05) with a coefficient of 0.508 regression, R2 25.8% and the value t calculate 3.486 > t table 2.030. Enhancement products will be 1 point would purchase decisions 0.426 points. Significantly to the influential business system purchasing decisions (p < 0.05) and the coefficient of regression, R2 0.569 32.4% and the value t calculate 4.099 > t table 2.030. The increase of business system 1 point then it will increase the purchasing decision 0.426. Influential business products and systems is significant against the decision of the buyer with the regression coefficient, R2 0.579 33.6% and test result F calculate 8.584 > F table 3.28. The conclusion of business products and systems effect significantly to purchase decisions either partially or simultaneous. It is suggested to the company to improve the quality of the products and the business system, maximizing the delivery of raw materials, improve discipline and partners held a meeting of the partners, it is useful to more attractive and convincing a partner against business products and systems in business franchise decisions.